Poszukiwanie form aktywności i aktywizacji seniorów - Mitkiewicz, Bartosz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article outlines the characteristics of activity and activation of senior citizens and highlights the personalistic dimension of this activity. It shows how physical activity can be used in building interpersonal relationships. Bearing in mind that each human being represents a physical, psychological and spiritual unity, it is suggested that the physical activity of senior citizens be approached from the perspective of personalistic philosophy as a source of inspiration for the activation of the elderly. Active ageing is mainly related to the areas of professional and social activity and a broadly defined quality of life based on good health and well-being. The term “active ageing” is increasingly being replaced by “successful ageing.” An indisputable element of the latter is staying active, with physical activity being a prerequisite for the overall functioning in the world. In old age, physical activity should be regarded as a necessity and a need for a peaceful, happy and healthy life.